PERBEDAAN TOKSISITAS EKSTRAK DAUN SIRIH (Piper betle L.) DENGAN EKSTRAK BIJI SRIKAYA (Annona squamosa L.) TERHADAP LARVA NYAMUK Aedes aegypti L. - Dwi Wahyuni; Intania Loren (saintifika, 2015)
Dengue Fever is a public health problem that is more widespread endemic area for morbidity is high enough into something that must be addressed immediately.The way to solve this desease chemically can make this mosquito becomes resistant. To solve this problem, it needs to find an alternative way in which it can be a natural insecticide that is safe like compounds that comes from Piper betle leaves and Annona squamosa seed. The active compounds of Piper betle leaves that are mixed with the active compounds of Annona squamosa seeds can be used as bioinsecticide. Piper betle leaves contain the active compounds of saponin, alkaloid, flavonoid and tannin, while Annona squamosa seeds contain theactive compounds of annonacin, squamocin, asimisin and alkaloid. This research aimsed to investigate the toxicity of themixture of the Piper betle leaves extract and Annona squamosa seeds againet Aedes aegypti mosquito larvae and tocompare the toxicity of the extract mixture and single extract. The method of this research used complete random design bythree repetitions. The concentratios used were 300, 600, 900, 1200 and 1500 ppm for Piper betle leaves extract and 5, 10, 50, 70 and 100 ppm for Annona squamosa seeds extract with aquades asthe control. The data were analyzed by using probit analysis to determine the LC50. The LC50 score of the Piper betle leaves extract was 910,38 ppm and the LC50 of the Annona squamosa seeds extract was 20,62 ppm. This result showed that toxicity of Piper betle leaves extract with different Annona squamosa seeds which was toxicity is higher than the toxicity of Piper betle leaves extract.